The Relationship between Parental Knowledge and Children's Anxiety Level in Tooth Extraction - Azizah Shofiyatul Fadhilah; Isnanto Isnanto; Bambang Hadi Sugito; Imam Sarwo Edi (International Journal of Advanced Health Science and Technology, 2023)
Anxiety is a psychological reaction to something unwanted. Dental anxiety is the thought that something scary will happen before someone has a dental visit or treatment. The results of the initial data collection related to anxiety about tooth extraction at SD Islam Maryam Surabaya, it is known that 86% of children experience severe anxiety. The study aims to determine the relationship between parental knowledge and children's anxiety levels in the act of removing teeth in class IV SD Islam Maryam Surabaya. The type of research used was analytic research with a cross-sectional design, with 65 class IV children as research subjects. Data collection method by means of a questionnaire. The data analysis technique uses the Chi Square test. The test results from the study obtained an Asymp.sig.(2-tailed) value of 0.000, which means that the p value (signification) is smaller than α (0.05) so that parental knowledge is related to the level of anxiety in the act of removing teeth in class IV SD Islam Maryam Surabaya. INDEX TERMS Knowledge, Anxiety, Tooth extraction